Correction: Melittin-encapsulating peptide hydrogels for enhanced delivery of impermeable anticancer peptides. (1st October 2020) - Feng, Jue-Ping; Zhu, Ru; Jiang, Fagang; Xie, Jie; Gao, Chang; Li, Min; Jin, Honglin; Fu, Dehao
Abstract : Correction for 'Melittin-encapsulating peptide hydrogels for enhanced delivery of impermeable anticancer peptides' by Jue-Ping Feng et al., Biomater. Sci., 2020, 8, 4559–4569, DOI: ; 10.1039/C9BM02080B .